The entomophagous caterpillar fungus Ophiocordyceps sinensis is consumed by its lepidopteran host as a plant endophyte. (October 2020) - Wang, Zhengyang; Li, Meng; Ju, Wenbin; Ye, Wenqing; Xue, Longhai; Boufford, David E.; Gao, Xinfen; Yue, Bisong; Liu, Yong; Pierce, Naomi E.
Abstract: Endophytic insect pathogenic fungi of the order Hypocreales reside in plant tissues as mutualistic partners that protect plants against insect herbivores. Caterpillar fungus Ophiocordyceps sinensis (order: Hypocreales, family: Ophiocordycipitaceae) is often described as an entomophagous fungus that parasitizes lepidopteran larvae of the ghost moth genus Thitarodes (family: Hepialidae), but recent evidence suggests involvement of a plant-endophytic stage in O. sinensis infection of insect larvae. In this study, we screen sample plant species in a caterpillar fungus collection site at Mt. Gongga, Sichuan, China, for endophytic O. sinensis and analyze the diet of Thitarodes larvae living in the soil of the same habitat. We show that the entomophagous caterpillar fungus O. sinensis is a prevalent plant endophyte (present in 52.6% of all plant genera and 66.7% of plant families) and that the presence of endophytic O. sinensis in plant leaf tissue is significantly correlated with its presence in plant root tissue. Our analysis of larval diet content reveals a high diversity generalist diet and confirms that the plant families harboring endophytic O. sinensis are consumed by Thitarodes larvae, although the composition and diversity of an individual's diet do not predict its level of fungal infection. These results suggest a reproductive strategy of O. sinensis involving a plant endophytic stage that facilitates infection of root-eating host larvae. Our study highlights the role of resident plant communities as a third participating partner in this complex symbiosis.